Strategic writing for UX drive engagement, conversion, and retention with every word - Podmajersky, Torrey (O'Reilly Media, 2019)
Now You're Having the Right Conversation4: Apply UX Text Patterns; Titles; Buttons, Links, and Other Commands; Descriptions; Empty States; Labels; Controls; Text Input Fields; Transitional Text; Confirmation Messages; Notifications; Errors; Summary: Use Patterns as a Place to Start; 5: Edit, Because They Didn't Go There to Read; Editing in Four Phases; Purposeful; Concise; Conversational; Clear; Summary: Use UX Text to Help People Move Forward; 6: Measuring UX Content Effectiveness; Direct Measurement of UX Content; Researching UX Content; UX Content Heuristics
Includes index. - Includes bibliographical references and index. - Online resource; title from PDF title page (EBSCO, viewed June 17, 2019)
Keywords: User interfaces (Computer systems) -- Design; COMPUTERS; User Interfaces; COMPUTERS; Programming Languages; Python; User interfaces (Computer systems); Design